Healthcare Students' Perceptions of the Quality of the Clinical Learning Environment in Morocco: A Cross-Sectional Study - Khadija Guejdad; Ali Ikrou; Camilla Strandell-Laine; Redouane Abouqal; Jihane Belayachi (Hindawi Limited, 2024)
Background. The clinical learning environment (CLE) is critical for developing the practical skills needed in healthcare professions. This study aimed to evaluate healthcare students' perceptions of the quality of the CLE using the Arabic version of the Clinical Learning Environment, Supervision and Nurse Teacher (ar. CLES + T) scale. The study also aimed to evaluate the tool's measurement invariance and compare perceptions among student groups. Methods. This cross-sectional study was carried out at two health education institutes in Morocco throughout the academic year 2018-2019 among 1550 undergraduate students who had just finished a clinical practicum in a hospital or primary healthcare facility. Data were gathered using the ar. CLES + T scale. Confirmatory factor analysis (CFA) and multigroup CFA were performed. The measurement invariance of the ar. CLES + T scale was assessed across gender, study year, and clinical practicum duration, using configural invariance, metric invariance, scalar invariance, and strict invariance. The t-test and analysis of variance were used to compare the mean scores of the student groups. Results. Students expressed positive perceptions toward the CLE. The "Pedagogical atmosphere on the ward" dimension scored the highest, while the "Role of the nurse teacher" dimension received the lowest scores. The measurement invariance of the ar. CLES + T scale by gender, study year, and clinical practicum duration was established. First-year students and those with an extended practicum period were the most satisfied. Conclusion. To promote effective learning in the clinical environment, nurse teachers might use innovative teaching approaches tailored to their evolving role in these settings. Moreover, extending the duration of clinical practicum can further enhance student learning outcomes.